To live and defy in LA how gangsta rap changed America - Viator, Felicia Angeja, 1978- (Harvard University Press, 2020)
"In its early days, rap was understood as the poetry of the "inner city," which usually meant New York. Few expected anything as hard-edged as gangsta rap to emerge from Los Angeles, home of surf and sun. Felicia Viator tells the story of LA's self-styled "ghetto reporters," whose music forced America to see an urban crisis it preferred to ignore"--